Development of ozone reactor for medicine base on Dielectric Barrier Discharge (DBD) plasma. (February 2019) - Zain, A Z; Restiwijaya, M; Hendrini, A R; Dayana, B; Yulianto, E; Kinandana, A W; Arianto, F; Sasmita, E; Azam, M; Sumariyah, S.; Nasrudin, N; Nur, M
Abstract: The development of the reactor for a lower concentration of ozone need to be done. The tipe of reactor can be used for the application of medical ozone therapy. Medical ozone therapy can be produced by using double DBD plasma reactor with oxygen as source and variation of voltage. The influence of flowrate to ozone capacity was investigated using double DBD plasma reactor with cylinder-cylinder configuration. The high AC voltage was applied in the range of 0-2000 Volts and the frequency of 50 Hz. The pure oxygen inserted into the reactor with several variations in flow rate, i.e. 2 to 10 L/min. The results showed that the ozone concentration decreased with increasing gas flow rate. I-V characteristic shows that reactor has two regime current as function of voltage. This characteristic is difference with single dielectric DBD Plasma reactor. The suitable dose of ozone therapy for medical other than useful in numerous pathological conditions could be a powerful therapeutic resource to prevent the damages of aging and to improve many functions in human bodies without deleterious effects.